Aru Shah and the nectar of immortality - Chokshi, Roshani; Riordan, Rick (Los Angeles : Disney/Hyperion, 2022)
The Pandavas call on old friends, make new allies, and face fearsome trials as they embark on a mission to stop the Sleeper from accessing the nectar of immortality. Ultimately Aru must decide who deserves immortality, the devas or the asuras, and an unexpected answer comes from an unexpected place.
"Rick Riordan presents."
Kirkus Starred, March 2022
5.4.
3-6.
Keywords: Hindu mythology -- Juvenile fiction; Immortality -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Adventure stories; Hindu mythology -- Fiction; Immortality -- Fiction; Voyages and travels -- Fiction; Supernatural -- Fiction; Adventure and adventurers -- Fiction; Mythological fiction; Paranormal fiction; Action and adventure fiction